Innovative Approach To Enhance Tribological Performance Of Conveyor Belt System. (2017) - Sharma, Mohit; Bhardwaj, Ayush; Cheong, Augustine
Abstract: The present case study reports the development of innovative method to reduce coefficient of friction between the conveyor belt systems against the metallic support. The process involves identification of suitable self-lubricating materials – Polytetrafluoroethylene (PTFE) and nylon in the fibrous form to develop modified conveyor belt with improved frictional performance i.e. reduction of coefficient of friction values. The stitching of PTFE fibers on the conveyor system with varying gauge diameter, spacing distance (pitch) and design to reduce the friction. The incorporation of fluorocarbon and/or nylon fibers with the rubber materials created a robust integrated conveyor system. With the stitching of PTFE fibers the frictional force reduced significantly which further reduces the coefficient of friction against the counter face steel component. The fibers are effectively incorporated with rubber and therefore no peeling or reduction in mechanical performance of conveyor belt system is observed. From the measured values, the frictional force can be lowered as much as 64 % for modified conveyor system. The series of samples were developed based upon the varying fiber gauge diameter and pitch further characterized for tribological performance in terms of coefficient of friction. Reduction in coefficient of friction was observed after incorporation of PTFE fibers. The current method is scalable and can be easily adopted for industrial practice.